Atomic Ni-catalyzed cathode and stabilized Li metal anode for high-performance Li–O2 batteries - Tiansheng Bai; Jiaxian Wang; Hongqiang Zhang; Fengjun Ji; Wei Song; Shenyi Xiao; Dandan Gao; Jingyu Lu; Lijie Ci; Deping Li (eScience)
The Li–O2 battery (LOB) has attracted growing interest, including for its great potential in next-generation energy storage systems due to its extremely high theoretical specific capacity. However, a series of challenges have seriously hindered LOB development, such as sluggish kinetics during the oxygen reduction and oxygen evolution reactions (ORR/OER) at the cathode, the formation of lithium dendrites, and undesirable corrosion at the lithium metal anode. Herein, we propose a strategy based on the ultra-low loading of atomic Ni catalysts to simultaneously boost the ORR/OER at the cathode while stabilizing the Li metal anode. The resultant LOB delivers a superior discharge capacity (> 16,000 ​mA​h ​g−1), excellent long-term cycling stability (> 200 cycles), and enhanced high rate capability (> 300 cycles @ 500 ​mA ​g−1). The working mechanisms of these atomic Ni catalysts are revealed through carefully designed in situ experiments and theoretical calculations. This work provides a novel research paradigm for designing high-performance LOBs that are useable in practical applications.